Time, Age, Change: Review of The Big Move by Anne Wyatt-Brown, Ruth Ray Karpen and Helen Q. Kivnick and Transitions and Transformations: Cultural Perspectives on Ageing and the Life Course. Edited by Caitrin Lynch and Jason Danely - Pickard, Susan (Age, Culture, Humanities: An Interdisciplinary Journal, 2018)
—